Long non-coding RNA EPB41L4A-AS1 as a biomarker of sepsis alleviates inflammatory response by targeting miR-146a-5p - Weigui Zhou; Chan Li; Huixian Yun; Ningning Zhang; Rui Zhang (European Journal of Medical Research)
Abstract Objective The prognosis of sepsis, a pathological condition associated with high mortality and rapid progression, can be improved with precise diagnosis, effective treatment, and nursing care. This study investigated the expression and clinical significance of the long non-coding RNA (lncRNA) EPB41L4A-AS1 in sepsis. Methods The serum EPB41L4A-AS1 levels in patients with sepsis were quantified using quantitative real-time polymerase chain reaction (RT-qPCR). The diagnostic value of EPB41L4A-AS1 was determined using the receiver operating characteristic curves. The correlation of EPB41L4A-AS1 with clinical parameters was evaluated using Pearson correlation. Kaplan–Meier assessment of prognostic value. Lipopolysaccharide (LPS)-treated THP-1 cells served as an in vitro cell model for sepsis. The mRNA and protein levels of inflammatory factors were examined using RT-qPCR analysis and enzyme-linked immunosorbent assay, respectively. Finally, the binding of EPB41L4A-AS1 to miR-146a-5p was determined using the dual-luciferase reporter and RNA immunoprecipitation assays. Results EPB41L4A-AS1 was significantly downregulated in patients with sepsis. The downregulation was inversely correlated with inflammatory cytokines and severity scores (APACHE II and SOFA). EPB41L4A-AS1 expression had a high diagnostic value in sepsis. The overexpression of EPB41L4A-AS1 downregulated inflammatory factor expression and release. However, miR-146a-5p mitigated the inhibitory effects of EPB41L4A-AS1 overexpression on inflammatory factors expression and release. EPB41L4A-AS1 was a target of miR-146a-5p. Conclusion lncRNA EPB41L4A-AS1 alleviates sepsis-related inflammation by targeting miR-146a-5p and may serve as a diagnostic biomarker for sepsis.